10.1016/s1541-9800(08)70365-x (CrossRef Listing of Deleted DOIs, 2000)
BACKGROUND: Previous studies have found no significant difference in birth weight between donor sperm and partner sperm, and some studies have found that donor sperm is more likely to lead to small for gestational age (SGA). OBJECTIVE: Does the use of donor sperm affect the birth weight of the offspring? MATERIALS AND METHODS: This study was a retrospective cohort study, including patients who achieved a singleton using in vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI) in fresh embryo transfer cycles in Peking University Third Hospital from January 2012 to December 2022. Birth weight and complete maternal baseline data were collected. A total of 3360 cycles were included in the study, of which 611 cycles used donor sperm and 2749 cycles used partner sperm from males with oligoasthenozoospermia. Multiple linear regression analysis and logistic regression analysis were performed to evaluate the possible relationship between donor sperm use and the birth weight of the offspring and the occurrence rates of large for gestational age (LGA), SGA, high birth weight (HBW), and low birth weight (LBW) in offspring. RESULTS: Comparing 611 cycles in which donor sperm was used with 2749 cycles in which partner sperm was used, baseline data did not differ significantly between the two groups in terms of female age, BMI, parity, and cause of infertility. Offspring born in the donor group had higher birth weight (p < 0.01) and Z score (p < 0.01) than those in the partner sperm. There were no differences in the incidence of LGA, SGA, HBW, LBW, preterm birth, and the proportion of offspring gender between the two groups. CONCLUSION: This study found that the babies born in the donor sperm cycles have higher birth weights than the use of partner sperm from males with oligoasthenozoospermia in fresh embryo transfer cycles, but there were no significant differences in LGA, SGA, HBW, and LBW. The research results suggest that we should pay attention to the safety issues of donor sperm. It is necessary to conduct further research to determine whether the cause of the increased birth weight is the sperm freezing technology or the factors of the male donors who provided the sperm.